2007
DOI: 10.3200/jmbr.39.3.162-168
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between the Sense of Self-Agency and Schizotypal Personality Traits

Abstract: People with schizotypal traits may possess abnormal self-awareness, particularly with regard to their sense of self-agency, that is, the sense that it is oneself who is causing or generating an action. Participants in Experiments 1A (N = 11), 1B (N = 12), and 2 (N = 20) moved a mouse device and viewed resultant feedback, which was biased either temporally or spatially. They then judged whether there was a bias or whether they felt they had moved the cursor on their own. The authors found, for the 1st time, tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
55
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 33 publications
9
55
2
Order By: Relevance
“…Several previous studies have observed non-clinical individuals high in schizotypy to show the same behavioral and neurophysiological deficits as found in patients with established schizophrenia, including deficits in sense of agency (Asai & Tanno, 2007; 2008), working memory (Ziermans, 2013; Chun et al, 2013), executive functioning (Kim et al, 2011), attention and prepulse inhibition (Giakoumaki, 2012), as well as resting state fMRI indicating a significant positive correlation between SPQ score and visual resting state networks and a significant negative correlation between SPQ score and auditory resting state networks (Lagioia et al, 2010). However, to our knowledge, the present study is the first to investigate N1-suppression to self-generated speech in the context of schizotypy.…”
Section: Discussionmentioning
confidence: 80%
“…Several previous studies have observed non-clinical individuals high in schizotypy to show the same behavioral and neurophysiological deficits as found in patients with established schizophrenia, including deficits in sense of agency (Asai & Tanno, 2007; 2008), working memory (Ziermans, 2013; Chun et al, 2013), executive functioning (Kim et al, 2011), attention and prepulse inhibition (Giakoumaki, 2012), as well as resting state fMRI indicating a significant positive correlation between SPQ score and visual resting state networks and a significant negative correlation between SPQ score and auditory resting state networks (Lagioia et al, 2010). However, to our knowledge, the present study is the first to investigate N1-suppression to self-generated speech in the context of schizotypy.…”
Section: Discussionmentioning
confidence: 80%
“…If this prediction does not match the feedback, the perceived sense of agency will decrease. For instance, previous studies suggest that delayed visual feedback when voluntarily handling tools decreases a sense of agency (Franck et al, 2001; Asai and Tanno, 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the authors had no means to modulate an induced sense of agency. To manipulate and investigate a sense of agency, previous studies adopted systematically delayed visual feedback of an action from an intact limb (Franck et al, 2001; Asai and Tanno, 2007). For instance, participants were asked to judge whether they felt they had produced the action outcome.…”
Section: Introductionmentioning
confidence: 99%
“…In this condition, position estimation was shifted by the illusion from this location away from the body, towards extracorporeal space (Out condition). This was compared a control condition that shifted felt position in towards the body (In Condition), in line with previous research Asai & Tanno, 2007;Heed et al, 2011). In this condition the position of the actual hand and false hand were swapped:…”
Section: New Evidence Suggests Original Models Of Rhi Mechanisms May mentioning
confidence: 97%
“…Traditionally, RHI experiments have been conducted with the participant's real hand displaced laterally away from the body midline, with the rubber hand located medially, towards the body -often in line with the approximate shoulder position Asai & Tanno, 2007;Heed et al, 2011). From these experiments it is clear that drift can be produced towards the body.…”
Section: New Evidence Suggests Original Models Of Rhi Mechanisms May mentioning
confidence: 99%